Psychoanalysis and Logotherapy in the Treatment of Obsessional Neurosis - Ovejas, Patricia (2012)
The integration of Psychoanalysis and Logotherapy in the diagnosis and treatment of obsessional neurosis. Purpose: Analyze the way the contributions of the Psychoanalysis and Logotherapy may be integrated when dealing with obsessive neurotics in a therapy. Methodology: A systematic review of the literature was conducted, adopting a critical perspective and taking as primary sources Freud, Lacan, Frankl and other psychoanalytic authors’ work. Conclusions: It is possiblefor a patient to undergo a psychoanalytic treatment model through transference technique and, based on that, to analyze his/her distorted ideas of the world and life from logotherapy.